TBM tunnelling under the Suez Canal – Port Said tunnels in challenging ground conditions. Issue 1 (15th February 2018) - Rizos, Dimitrios; Williams, Derek; Fouda, Ahmed; Amin, Tarek; Aboudshiesh, Mohamed; Nicola, Anis Dimitry
Abstract: The Port Said Tunnels Project consists of twin road tunnels crossing the Suez Canal with a planned capacity of 2, 100 mixed vehicles/hour in each direction. The dual carriageway tunnels are an important part of the Suez Canal Region Development Plan, which will connect the Sinai with other Egyptian provinces to provide a gateway for investment opportunities and speed up the development of Sinai province. The project is located 19 km south of Port Said city, near the northern entrance of the Suez Canal. The tunnels are constructed using slurry shield TBMs in difficult ground conditions, including the presence of methane gas. This paper demonstrates the main challenges encountered during tunnelling and the measures taken to mitigate potential risks during construction and to control long‐term differential settlements in the upper, very soft soil. The tunnels are connected by two cross passages which are being constructed using ground freezing and conventional tunnelling.